Climate Change Risks to the Soybean Value Chain in Ethiopia: Proactive Actions for Resilience in the Ethiopian Food System Resilience Program Districts - International Maize and Wheat Improvement Center (International Maize and Wheat Improvement Center, 2024)
Soybean, an economically important and rising cash crop in Ethiopia, is evidently challenged by climate change and variability. The projected risks posing threats to the soybean value chain are: • By 2035, rainfall in soybean-producing areas is projected to increase by 57-210 mm across the soybean-growing areas with an increased variability by up to 17%. • Maximum and minimum temperatures in soybean-producing areas will increase by 0.84-1.310C and 1.13-1.520C , respectively. • Rainfall extremes such as the number of rainy, heavy rain and very heavy rain days, and consecutive wet days will increase. • Temperature extremes such as hot days and hot nights will increase, and diurnal temperature ranges will decline. Alterations in key climatic variables will have several socio-economic and environmental implications that demand proactive actions.